Direct-drive target designs as energetic particle sources for the Laser MégaJoule facility. (18th March 2021) - Temporal, Mauro; Canaud, Benoit; Ramis, Rafael
Abstract : This work aims to analyse the possibility of directly driven imploding spherical targets in order to create a source of energetic particles (neutrons, protons, alphas, tritium and 3 He ions) for the Laser MégaJoule facility. D 3 He gas-filled spherical SiO2 glass pellets, irradiated by an absorbed laser intensity of 10 14 W cm −2 or 10 15 W cm −2 have been considered. Depending on the absorbed laser intensity and the amount of the ablated glass layer two distinct regimes have been identified: a massive pusher and an exploding pusher . Both regimes are analysed in terms of hydrodynamics and fast particle spectra. Energetic particle time-resolved spectra are calculated and used to infer ionic temperatures and total areal densities. A parametric study has been performed by varying the shell thickness and target inner radius for both laser absorbed intensities.